2011
DOI: 10.1371/journal.pone.0024579
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Surveillance among Outpatients and Inpatients in Morocco, 1996–2009

Abstract: BackgroundThere is limited information about the epidemiology of influenza in Africa. We describe the epidemiology and seasonality of influenza in Morocco from 1996 to 2009 with particular emphasis on the 2007–2008 and 2008–2009 influenza seasons. Successes and challenges of the enhanced surveillance system introduced in 2007 are also discussed.MethodsVirologic sentinel surveillance for influenza virus was initiated in Morocco in 1996 using a network of private practitioners that collected oro-pharyngeal and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 19 publications
6
46
1
1
Order By: Relevance
“…Children below 5 years of age comprised of 35% of all patients enrolled in this study while the RSV detection rate in children under 5 years of age was 76%. This rate was high compared to the findings reported in USA and Turkey with 18% and 24.5% respectively (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).Similar to our findings, Weber et al reported higher percentage of RSV-infection in children less than 6 months of age in developing countries (16). In this study, the higher percentage of RSV infection among infants may probably be due to nosocomial spread of the virus within paediatric care units during the high circulating season of RSV.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Children below 5 years of age comprised of 35% of all patients enrolled in this study while the RSV detection rate in children under 5 years of age was 76%. This rate was high compared to the findings reported in USA and Turkey with 18% and 24.5% respectively (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).Similar to our findings, Weber et al reported higher percentage of RSV-infection in children less than 6 months of age in developing countries (16). In this study, the higher percentage of RSV infection among infants may probably be due to nosocomial spread of the virus within paediatric care units during the high circulating season of RSV.…”
Section: Discussioncontrasting
confidence: 63%
“…In temperate climate, RSV usually circulates during the winter season from November to April. Epidemics of RSV occurs when the circulation of influenza virus peak in the period from October through April (9). Although no clear seasonal pattern on the circulation of RSVs could be gathered from these data, the detection rate for RSV-positive infection was highest from November to March every year (during the fourth and the first quarter; P <0.001) while the detection rate was observed to have peaked in our study during week 52 of 2014 and week 3 of 2016.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the fact that our incidence estimation is based on data from one year and from three hospitals only while in all these countries, data were collected over a period of three to one year while the data on influenzavirus positivity in all these countries are over a period of 3 to 5 years and since we know that the pre-dominant patterns of seasonal influenza virus keeps on changing, there is no surprise that while we found the influenza A (H3N2) virus to be predominantly circulating in 2013 in our study, in all these countries, the iinfluenza A/H1N1 was the predominant virus subtype co-circulating with influenza A/H3N2. However, what we noticed that the influenza seasonal pattern that we observed in Egypt mimic more closely with Tunisia and Morocco (22) In our study, we found out that the percentage of influenza-positivitty influenza positivity rate was detected amongst SARI cases, not all patients were sampled systematically and different sampling techniques were applied to collect either the nasopharyngeal or oropharyngeal swab.…”
Section: Influenza Incidencementioning
confidence: 59%
“…In line with the WHO Global Agenda for Influenza Surveillance and Control, Morocco strengthened influenza sentinel surveillance in 2007. As a result 3102 respiratory samples were collected between 2007–2009 with 98 (3%) of these samples positive for influenza (20). The emergence of the 2009 H1N1 pandemic led to increased surveillance resulting in the collection of 3937 samples between June 2009 and February 2010 alone (15).…”
Section: North Africamentioning
confidence: 99%